2020
DOI: 10.1039/d0ta04863a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of low intensity light performances of kesterite CZTSe, CZTSSe, and CZTS thin film solar cells for indoor applications

Abstract: Three kesterite thin-film solar cells, Cu2ZnSnSe4 (CZTSe), Cu2ZnSn(S,Se)4 (CZTSSe), and Cu2ZnSnS4 (CZTS), and based on low light intensity measurements, examined the possibility of using kesterite devices for indoor applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Based on our previous report, a faster V OC loss under low‐intensity light conditions was mainly caused by deep‐level defects in the bulk of the photo absorber. [ 32 ] It is well known that J SC has a linear relationship with light intensity, whereas the V OC has a logarithmic relationship with light intensity, so faster V OC loss under low‐intensity light condition is closely related to deep‐level defects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous report, a faster V OC loss under low‐intensity light conditions was mainly caused by deep‐level defects in the bulk of the photo absorber. [ 32 ] It is well known that J SC has a linear relationship with light intensity, whereas the V OC has a logarithmic relationship with light intensity, so faster V OC loss under low‐intensity light condition is closely related to deep‐level defects.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous report, we successfully demonstrated the comparative performance of Cu 2 ZnSnS 4 (CZTS), Cu 2 ZnSnSe 4 (CZTSe), and CZTSSe solar cells under low‐intensity light conditions, and revealed that CZTSSe demonstrated better power output in the condition. [ 32 ] Nevertheless, we found that the performance of CZTSSe under low light conditions is mainly limited by the deep‐level defect‐assisted carrier recombination. To overcome this limitation, in this study, Ag and Ge were doped to CZTSSe to lessen deep‐level defects, and the performance of the doped CZTSSe samples under indoor light conditions was evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…When the ratios of Sn 4þ to Sn 2þ was 1:0 and 0:1, the average roughness was 91.46 and 99.26 nm. According to the literature, [30,[33][34][35][36][37] the rough CZTSSe films have a comparatively high number of defects in the heterojunction region, which acts as an interfacial recombination center. The smaller roughness indicates the better film surface quality of absorption layer, which is beneficial for the growth of the much better and more uniform CdS film with the same chemical bath deposition (CBD) process, showing superior heterojunction quality.…”
Section: Resultsmentioning
confidence: 99%
“…The indoor lights are usually weak in all directions, which are difficult to be effectively utilized. The reported substrate-structured Mo-based CZTSSe solar cells exhibited good performance under low-light conditions 20 but limited by light directions. Bifacial solar cells have unique advantages in collecting front and rear illuminations, reducing the solar cell cost in a photovoltaic system by efficiently utilizing materials and areas 21 23 .…”
Section: Introductionmentioning
confidence: 99%